Production of mouse monoclonal antibody against Streptococcus dysgalactiae GapC protein and mapping its conserved B-cell epitope. (February 2015) - Zhang, Limeng; Zhang, Hua; Fan, Ziyao; Zhou, Xue; Yu, Liquan; Sun, Hunan; Wu, Zhijun; Yu, Yongzhong; Song, Baifen; Ma, Jinzhu; Tong, Chunyu; Zhu, Zhanbo; et al.
Highlights: The mAb1E11 against S. dysgalactiae GapC was successfully generated. The motif 97 TGFFAKK 103 is an epitope of the S. dysgalactiae GapC. Our findings are available for further study of epitope-based vaccines. Abstract: Streptococcus dysgalactiae ( S. dysgalactiae ) GapC protein is a protective antigen that induces partial immunity against S. dysgalactiae infection in animals. To identify the conserved B-cell epitope of S. dysgalactiae GapC, a mouse monoclonal antibody 1E11 (mAb1E11) against GapC was generated and used to screen a phage-displayed 12-mer random peptide library (Ph.D.-12). Eleven positive clones recognized by mAb1E11 were identified, most of which matched the consensus motif TGFFAKK. Sequence of the motif exactly matched amino acids 97–103 of the S. dysgalactiae GapC. In addition, the epitope 97 TGFFAKK 103 showed high homology among different streptococcus species. Site-directed mutagenic analysis further confirmed that residues G98, F99, F100 and K103 formed the core of 97 TGFFAKK 103, and this core motif was the minimal determinant of the B-cell epitope recognized by the mAb1E11. Collectively, the identification of conserved B-cell epitope within S. dysgalactiae GapC highlights the possibility of developing the epitope-based vaccine.